2020
DOI: 10.1002/esp.5031
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of shear stress and friction in the surf zone

Abstract: Measurements of near‐bed shear stress were undertaken in the shallow subtidal zone at Durras Beach, NSW, Australia using a sideways‐looking acoustic velocity meter installed within the wave boundary layer. The wave climate was swell‐dominated and wave conditions comprised shoaling and breaking waves as well as surf bores. The sediment at the field site was medium‐grained sand, and observations of bedform geometry were conducted using a pencilbeam‐sonar system. Using frequency‐filtering techniques, the measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…It is clear, however, that such imposed cut-off frequencies do not uniquely define, for example, the gravity wave and turbulence frequency bands since gravity wave motion may leak into frequencies above the cut-off, and largescale turbulent motions may exist at frequencies below the cut-off such that an overlap region must be expected. However, the cut-off should identify the spectral bandwidths where the respective motions (wave orbital vs. turbulent) are dominant [36]. Alternatively, Bricker and Monismith [37] devised a phase-method operating in the spectral domain that produced satisfactory results in cases when the wave-induced strain field was weaker than the turbulence strain field.…”
Section: Turbulence Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear, however, that such imposed cut-off frequencies do not uniquely define, for example, the gravity wave and turbulence frequency bands since gravity wave motion may leak into frequencies above the cut-off, and largescale turbulent motions may exist at frequencies below the cut-off such that an overlap region must be expected. However, the cut-off should identify the spectral bandwidths where the respective motions (wave orbital vs. turbulent) are dominant [36]. Alternatively, Bricker and Monismith [37] devised a phase-method operating in the spectral domain that produced satisfactory results in cases when the wave-induced strain field was weaker than the turbulence strain field.…”
Section: Turbulence Measurementmentioning
confidence: 99%
“…Even for strongly breaking waves (γ s > 0.67), <k> was maximum at the seabed, thus overwhelming surface-generated turbulence. When wave-driven longshore currents are strong, wave/current interaction in the bottom boundary layer increases bed shear stress relative to situations without longshore currents [36] and may conceivably also lead to <k>-maxima near the seabed. Considering effects of wave breaker type, observations have shown that for spilling breakers and surf bores, the vertical mixing is slower compared to plunging breakers and <k> tends to decrease more rapidly towards the bed [42,78,79], see also Figure 7.…”
Section: Turbulence Generation Spatial Structure and Magnitudementioning
confidence: 99%